Sámi Gastronomy: the Role of Traditional Knowledge - Sara, Ravdna Biret Marja Eira; Mathiesen, Svein Disch (Journal of Gastronomy and Tourism, 2020)
Traditional knowledge in food security is important for achieving sustainable food production systems. One example of food security is tenderness and meat quality. This article investigates the lack of Sámi reindeer herders' knowledge of meat tenderness and explores its relation to gastronomy and food sovereignty. Sámi family-produced reindeer meat is regarded as tender, while such meat is rarely available for visiting tourists. Therefore, a multidisciplinary approach combines different knowledge of meat tenderness in this article. When slaughtering in cold temperatures, a common slaughtering procedure is performed: dievás njuovvat (slaughtering reindeer outdoors on the ground) and bakkahit (a deliberate action of reindeer herder to leave the rumen inside the reindeer for tenderization). Decrease in intramuscular pH in sirloin, longissimus dorsi , from the baggan reindeer supports Sámi traditional knowledge of highquality meat. In the Sámi language there are a variety of concepts that include knowledge of slaughtering practices and quality of meat. This is the first scientific study of Sámi reindeer herders' traditional knowledge and their specialist language of reindeer meat quality. The Sámi language is a prerequisite for the food sovereignty governed by Sámi reindeer herders' families through generations, regardless of state policies and modernization. Everyday food from Sámi households could offer an important template for future Sámi gastronomy, and lead to stronger food sovereignty and improved food for visiting tourists.